The spirit of cities : why the identity of a city matters in a global age - Bell, Daniel (Daniel A.), 1964- (Princeton University Press, 2013)
Cities shape the lives and outlooks of billions of people, yet they have been overshadowed in contemporary political thought by nation-states, identity groups, and concepts like justice and freedom. The Spirit of Cities revives the classical idea that a city expresses its own distinctive ethos or values. In the ancient world, Athens was synonymous with democracy and Sparta represented military discipline. In this original and engaging book, Daniel Bell and Avner de-Shalit explore how this classical idea can be applied to today's cities, and they explain why philosophy and the social sciences.